Distinct IL‐1α‐responsive enhancers promote acute and coordinated changes in chromatin topology in a hierarchical manner. (7th November 2019) - Weiterer, Sinah‐Sophia; Meier‐Soelch, Johanna; Georgomanolis, Theodore; Mizi, Athanasia; Beyerlein, Anna; Weiser, Hendrik; Brant, Lilija; Mayr‐Buro, Christin; Jurida, Liane; Beuerlein, Knut; Müller, Helmut; Weber, Axel; et al.
Abstract: How cytokine‐driven changes in chromatin topology are converted into gene regulatory circuits during inflammation still remains unclear. Here, we show that interleukin (IL)‐1α induces acute and widespread changes in chromatin accessibility via the TAK1 kinase and NF‐κB at regions that are highly enriched for inflammatory disease‐relevant SNPs. Two enhancers in the extended chemokine locus on human chromosome 4 regulate the IL‐1α‐inducible IL8 and CXCL1‐3 genes. Both enhancers engage in dynamic spatial interactions with gene promoters in an IL‐1α/TAK1‐inducible manner. Microdeletions of p65‐binding sites in either of the two enhancers impair NF‐κB recruitment, suppress activation and biallelic transcription of the IL8 / CXCL2 genes, and reshuffle higher‐order chromatin interactions as judged by i4C interactome profiles. Notably, these findings support a dominant role of the IL8 "master" enhancer in the regulation of sustained IL‐1α signaling, as well as for IL‐8 and IL‐6 secretion. CRISPR‐guided transactivation of the IL8 locus or cross‐TAD regulation by TNFα‐responsive enhancers in a different model locus supports the existence of complex enhancer hierarchies in response to cytokine stimulation that prime and orchestrate proinflammatory chromatin responses downstream of NF‐κB. Synopsis: ATAC‐seq, native 4C‐seq and CRISPR genome editing reveal functional hierarchies and chromatin looping dynamics of cytokine‐inducible "master" enhancers that govern gene regulation during the early proinflammatory response. IL‐1α exposure remodels genome‐wide chromatin accessibility via TAK1 and NF‐κB. Multiple dynamic and pre‐established 3D chromatin interactions facilitate the IL‐1α response. Single‐enhancer deletion or activation reveal hierarchical control of the major human chemokine locus and inflammatory secretome. Prelooped enhancers act across TADs to repress or activate TNFα‐regulated genes. Abstract : ATAC‐seq, native 4C‐seq and CRISPR genome editing reveal functional hierarchies and chromatin looping dynamics of cytokine‐inducible "master" enhancers that govern gene regulation during the early proinflammatory response.